Association of maternal late-gestation lipid mobilization and their offspring's disease risk during the pre-weaned period and performance through first lactation: A cohort study in a dairy herd - Velasquez-Munoz, Ana; Schuurmans, Emily J.; Brester, Jill L.; Starken, Kathryn; Abuelo, Angel (Frontiers in Veterinary Science, 2023)
Excessive maternal lipid mobilization in late gestation may impact the immune function of the newborn but its long-term effects remain unknown. The objective was to explore associations between excessive maternal lipid mobilization in the last 2 weeks of gestation with offspring health and performance. A retrospective study was performed including 1,511 calves (heifer=692, bull=819) born 2015-2020 in one farm. Plasma non-esterified fatty acids (NEFA) was measured from cows 7 to 14 d before calving. Calves were categorized in 2 groups based NEFA concentration: physiological lipid mobilization (PLM=1,373; NEFA<0.3mM) and excessive lipid mobilization (ELM=138; NEFA≥0.3mM). Calf records were obtained from the herd's software. Outcomes of interest were the hazard of pre-weaned digestive and respiratory disease, pre-weaned ADG, age at first breeding and calving, first lactation 305d mature equivalent milk yield, and survival until first calving. Statistical models included dam NEFA category adjusted by year and season of birth, dam parity, and calf sex. Cox proportional analysis was used to determine the hazard of a pre-weaned health event, first breeding, and first calving. Linear regression was used to evaluate ADG and 305ME. The survival until first calving was analyzed with logistic regression. No difference was detected in the hazard of diarrhea (HR=1.06; 95%CI=0.82-1.38) and respiratory disease (HR=1.29; 95%CI=0.79-2.10) by NEFA category in the pre-weaned period. Also, no difference was detected for the LSM (±SE) of pre-weaned ADG (PLM=0.77±1.55, ELM=0.72±2.76 kg/d). In heifers, the hazard for first breeding favored the PLM group (HR=1.59; 95%CI=1.18-2.12), with a reduced median age at first breeding (PLM=400d, 95%CI=397-402; ELM=412d, 95%CI=404-421)). However, NEFA category was not associated with the hazard of first calving (HR=0.94; 95%CI=0.69-1.27), first lactation 305ME (PLM=16,665±165 kg; ELM=16,256±532), the odds of presenting at least 1 health event in the first lactation (OR=0.78; 95%CI= 0.41-1.49), or the odds of leaving the herd before first calving (OR=1.21; 95%CI= 0.56-2.02). Overall, dam ELM affected the hazard of first breeding but no other indicators of health or long-term performance. However, associations between maternal lipid mobilization and calf outcomes cannot be excluded, as the NEFA cut-off used has not been established as a predictor of offspring health and performance.